فعالية تنفيذ الطريقة السمعية الشفوية بوسيلة كتاب الفطرة العربية لترقية مهارة الكلام لطلاب الصف العاشر - Burhan Lukman Syah; Muhammad Afiq Bin Mohammad Sukhri (AL LUGHAH, 2023)
AbstractThe basic goal of learning Arabic is the ability of students to express Arabic correct expressions orally or with a pen and with what is read and what is heard. And Teaching Arabic in this digital age needs to develop its teaching method, one of these method is the Audiolingual. And uses the Fitrah Al-Arabiyah book to teach it. To find out the effectiveness of this method, the researcher implemented it in the ten grade students at Madrasah Aliyah of Al Azhar Islamic 24 Boarding School Cigombong Bogor in academic year 2021/2022. The researcher used the Classroom Action Research method, in terms of it has a tangible effect to know raising students’ speaking Arabic. Factors for knowing the skill of student speaking are the correct pronunciation of letters, the correct pronunciation of short and long characters, punctuality to intoning letters, eloquence. in order to obtain the required data, the researcher used the test method, observation, and written documents. And the results of this research are: The Audiolingual Method was able to make students speak Arabic while learning. The Audiolingual Method was able to increase students speaking skill as evidenced after adopting the audiolingual method and uses the Fitrah Al-Arabiyah book, exam after test was passed the students ability by comparison 20,8% The student is getting excellent results, and 41,7% the student is getting good results, and 16,7% enough results, and 20,8% students who didn’t graduate. And in the second cycle from pretest and posttest, increase students' speaking ability by comparison 9 students or 37,5% the students is getting excellent results, and 15 students or 62,5% the students is getting good results, and there are no students who don't pass.Keywords: The Audiolingual Method, Arabic learning, Fitrah Arabic Book.